Inquérito sorológico para Leishmania spp., Toxoplasma gondii, Trypanosoma cruzi e Neospora caninum em cães comunitários em Curitiba-Paraná, Brasil - Constantino, Caroline; Pellizzaro, Maysa; de Paula, Edson Ferraz Evaristo; Vieira, Thállitha Samih Wischral Jayme; Brandão, Ana Pérola Drulla; Ferreira, Fernando; Vieira, Rafael Felipe da Costa; Langoni, Helio [UNESP]; Biondo, Alexander Welker (FapUNIFESP (SciELO), 2016)
Neighborhood dogs may act as reservoirs for several zoonotic protozoan infections, particularly in urban areas, thus constituting a potential public health threat. Accordingly, the aim of the present study was to evaluate the exposure of neighborhood dogs to four protozoan pathogens in public areas with high levels of human movement in Curitiba, southern Brazil. Blood samples from 26 neighborhood dogs were screened by means of the indirect immunofluorescent antibody test (IFAT) for Leishmania spp., Toxoplasma gondii, Trypanosoma cruzi and Neospora caninum, and a questionnaire was answered by the respective keeper. A total of 8/26 dogs (30.7%) seroreactive to T. gondii, 3/26 (11.5%) to N. caninum and 2/26 (7.7%) to both were identified. All the samples were seronegative for T. cruzi and Leishmania spp. Pathogen seroreactivity was not associated with the daily human movements or other epidemiological variables investigated (p > 0.05). In conclusion, the low seroprevalence for T. gondii and N. caninum indicated low environmental and food risk for animal infection and the seronegativity for Leishmania spp. and T. cruzi may reflect the absence of these pathogens in urban areas of Curitiba. Moreover, neighborhood dogs may be used as environmental sentinels for the presence of protozoan pathogens and their vectors.
Serosurvey for leishmania spp., toxoplasma gondii, trypanosoma cruzi and neospora caninum in neighborhood dogs in Curitiba-Paraná, Brazil
Keywords: Community dogs; IFAT; Neosporosis; Sentinel animals; Toxoplasmosis; Urban area